2010
DOI: 10.1007/s11630-010-0245-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of aluminum micro channel heat sink

Abstract: Microchannel heat sinks constitute an innovative cooling technology for the removal of a large amount of heat from a small area and are suitable for electronics cooling. In the present work, Tool Steel D2 grade milling slitting saw type plain milling cutter is fabricated The microchannels are machined in aluminum work pieces to form the microchannel heat sink using the fabricated milling cutter in an horizontal milling machine. A new experimental set-up is fabricated to conduct the tests on the microchannel he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Microchannel heat sinks (MCHS) are capable of enhancing heat transfer rate due to their high surface to volume ratio relative to the conventional heat sinks. [1][2][3][4][5][6] Tuckerman and Pease demonstrated that heat transfer rate in MCHS (up to 790 W/cm 2 ) are significantly greater than macroscale heat sinks (20 W/cm 2 ). 7 However, increase in the heat transfer surface area yields the penalty of increased pressure drop.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microchannel heat sinks (MCHS) are capable of enhancing heat transfer rate due to their high surface to volume ratio relative to the conventional heat sinks. [1][2][3][4][5][6] Tuckerman and Pease demonstrated that heat transfer rate in MCHS (up to 790 W/cm 2 ) are significantly greater than macroscale heat sinks (20 W/cm 2 ). 7 However, increase in the heat transfer surface area yields the penalty of increased pressure drop.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the volumetric heat generation rate in electronic components increases steadily, and thermal management is vital due to capability of eliminating possible failures. Microchannel heat sinks (MCHS) are capable of enhancing heat transfer rate due to their high surface to volume ratio relative to the conventional heat sinks 1‐6 . Tuckerman and Pease demonstrated that heat transfer rate in MCHS (up to 790 W/cm 2 ) are significantly greater than macroscale heat sinks (20 W/cm 2 ) 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that heat flux could be removed from 256 W/cm 2 to 350 W/cm 2 for a nearly optimized microchannel, and the pumping power increased from 0.205 W to 5.365 W as well. Farnam et al (2009) analyzed the thermal performance of a microchannel heat sink to cool a chip with output power of 100 W. An experimental system was fabricated by Kumaraguruparan and Sornakumar (2010) to conduct tests on the heat transfer coefficient, pressure drop, friction factor and thermal resistance of a microchannel heat sink. Steinke et al (2006) also developed an experimental facility for investigation of single-phase liquid flow in microchannels.…”
Section: Introductionmentioning
confidence: 99%